Методика розслідування незаконного використання з метою отримання прибутку гуманітарної допомоги, благодійних пожертв або безоплатної допомоги : автореферат дисертації - Шевців , В. М.; Shevtsiv, V. M.; Глобенко, Г. І. - науковий керівник (Харків : Харківський національний університет внутрішніх справ, 2023)
Проаналізовано наукові підходи до формування криміналістичної характеристики як невід’ємного елемента окремої криміналістичної методики. Визначено сутність і з’ясовано значення криміналістичної характеристики незаконного використання з метою отримання прибутку гуманітарної допомоги, благодійних пожертв або безоплатної допомоги. Наведено структурні елементи криміналістичної характеристики досліджуваних кримінальних правопорушень (предмет, типові способи, час, місце, обстановка і типові сліди, особа злочинця) та розкрито їх зміст. Сформульовано криміналістичні рекомендації щодо розслідування цього виду кримінального правопорушення з урахуванням принципів періодизації, ситуативної зумовленості та алгоритмізації. Систематизовано обставини, що підлягають з’ясуванню під час розслідування незаконного використання з метою отримання прибутку гуманітарної допомоги, благодійних пожертв або безоплатної допомоги. Типізовано слідчі ситуації початкового та наступного етапів розслідування досліджуваного виду кримінального правопорушення. Наведено криміналістичні рекомендації щодо тактики проведення окремих процесуальних дій та встановлено особливості використання можливостей судових експертиз.

The theoretical generalization and a new solution to a scientific problem that is manifested in the development of a methodology for investigating the illegal use of humanitarian aid, charitable donations or free aid for profit have been provided. Scientific approaches to the formation and implementation of forensic characteristics as an integral element of a separate forensic methodology have been analyzed. The structural elements of the forensic characteristics of the investigated criminal offenses have been named (subject, typical methods, time, place, environment and typical traces, the person of the criminal) and their content has been disclosed. Forensic recommendations for the investigation of the illegal use of humanitarian aid, charitable donations or free aid for profit have been formulated, taking into account the principles of periodization, situational conditioning and algorithmization. The circumstances to be clarified in the course of investigation of illegal use of humanitarian aid, charitable donations or free aid for profit have been systematized and characterized. Typical methods of illegal use of humanitarian aid, charitable donations or free aid for profit have been defined as a system of actions of the offender united by a single criminal and illegal intention of its preparation, direct execution and concealment. It has been emphasized that the establishment and generalization of all structural elements of the method of committing a criminal offense of a separate category increases its cognitive function. It has been found that the illegal use of humanitarian aid, charitable donations or free aid for profit is most often committed in the following areas: providing assistance to the Armed Forces of Ukraine, other military formations, law enforcement agencies, state authorities during the legal regime of martial law to promote defense capability and mobilization readiness of the country, protection of the population; providing assistance to citizens who suffered as a result of the legal regime of martial law; providing assistance to healthcare institutions. It has been established that perpetrators of the illegal use of obtaining profit from humanitarian aid for profit, charitable donations or free assistance are citizens of Ukraine, men, aged 29–39, with higher and professional pre-higher education, who have work. Forensic recommendations regarding the investigation of the creation, management of a criminal community or criminal illegal use of humanitarian aid, charitable donations or gratuitous aid for profit have been formed, taking into account the principles of periodization, situational conditioning and algorithmization. Investigative situations of the initial and subsequent stages of the investigation of illegal use for profit of humanitarian aid, charitable donations or free aid have been typified. Algorithms of the investigator’s actions have been proposed. Forensic recommendations have been provided on the tactics of preparation, direct conduct and recording of the course and results of inspection, search, interrogation, covert investigative (search) actions (audio and video monitoring of a person, removal of information from transport telecommunication networks, observation of an object or place in publicly accessible places, control over the commission of a crime in the form of a special investigative experiment), separate measures to ensure criminal proceedings (obtaining temporary access to things and documents, imposing an arrest on property) and using the possibilities of forensic examinations during the investigation of illegal use of humanitarian aid, charitable donations or free aid for profit.

Определена сущность и установлено значение криминалистической характеристики незаконного использования с целью получения прибыли гуманитарной помощи, благотворительных пожертвований или безвозмездной помощи. Приведены структурные элементы криминалистической характеристики изучаемых уголовных правонарушений (предмет, типовые способы, время, место, обстановка и типовые следы, личность преступника) и раскрыто их содержание.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Methodology for Investigating the Illegal Use of Humanitarian Aid, Charitable Donations or Free Aid for Profit
Keywords: 12.00.09; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; криміналістика; розслідування кримінальних правопорушень; незаконне використання з метою отримання прибутку гуманітарної допомоги, благодійних пожертв або безоплатної допомоги; гуманітарна допомога; криміналістична характеристика; криміналістична методика; investigation of criminal offences; illegal use of humanitarian aid, charitable donations or free aid for profit; forensic characteristics; forensic methodology; расследование уголовных правонарушений; незаконное использование в целях получения прибыли гуманитарной помощи, благотворительных пожертвований или безвозмездной помощи; криминалистическая характеристика; криминалистическая методика